Digital encounters : envisioning connectivity in Latin American cultural production - Raynor, Cecily; Lewis, Rhian (M.A.) (Latinoamericana (Toronto, Ont.), 2023)
"To understand the creative fabric of digital networks, scholars of literary and cultural studies must turn their attention to crowdsourced forms of production, discussion, and distribution. Digital Encounters explores the influence of an increasingly networked world on contemporary Latin American cultural production. Drawing on a spectrum of case studies, the contributors to this volume examine literature, art, and political activism as they dialogue with programming languages, social media platforms, online publishing, and geospatial metadata. Implicit within these connections are questions of power, privilege, and stratification. The book critically examines issues of inequitable access and data privacy, technology's capacity to divide people from one another, and the digital space as a site of racialized and gendered violence. Through an expansive approach to the study of connectivity, Digital Encounters illustrates how new connections--between analog and digital, human and machine, print text and pixel--alter representations of self, Other, and world."--